2019
DOI: 10.1002/jccs.201900135
|View full text |Cite
|
Sign up to set email alerts
|

Construction of direct Z‐scheme g‐C3N4/TiO2 nanorod composites for promoting photocatalytic activity

Abstract: Direct Z‐scheme g‐C3N4/TiO2 nanorod composites were prepared for enhancing photocatalytic activity for pollutant removal. The characterization revealed that the g‐C3N4/TiO2 nanorod composite formed a close interface contact between g‐C3N4 and TiO2 nanorods, which was of benefit for the charge transfer and resulted in its high photocatalytic activity. The g‐C3N4/TiO2 nanorod composites exhibited higher photocatalytic activity for degradation of Rhodamine B (RHB) than bare g‐C3N4 and TiO2 nanorods. The high phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…[38] The secondary calcination samples show a significant blueshift compared to the once-calcined α-Fe 2 O 3 /ML g-C 3 N 4 , possibly because the secondary calcination of g-C 3 N 4 peels off into fewer layers, resulting in a quantum confinement effect. [14,18,39] While that of various α-Fe 2 O 3 /FL g-C 3 N 4 exhibit an apparent redshift, the redshift is increasingly enhanced with the increase of α-Fe 2 O 3 content. The enhancement of the visible light absorption intensity provides a possibility of improving the photocatalytic activity of α-Fe 2 O 3 /FL g-C 3 N 4 in the visible region.…”
Section: Optical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…[38] The secondary calcination samples show a significant blueshift compared to the once-calcined α-Fe 2 O 3 /ML g-C 3 N 4 , possibly because the secondary calcination of g-C 3 N 4 peels off into fewer layers, resulting in a quantum confinement effect. [14,18,39] While that of various α-Fe 2 O 3 /FL g-C 3 N 4 exhibit an apparent redshift, the redshift is increasingly enhanced with the increase of α-Fe 2 O 3 content. The enhancement of the visible light absorption intensity provides a possibility of improving the photocatalytic activity of α-Fe 2 O 3 /FL g-C 3 N 4 in the visible region.…”
Section: Optical Propertiesmentioning
confidence: 98%
“…Moreover, the Z-scheme photocatalytic system with a step-wise charge-transfer pathway, which is different from the widely used solid junction, not only favors photogenerated charge separation but also maintains excellent redox capacity of the two constituent semiconductors. [16][17][18][19][20] α-Fe 2 O 3 , especially with tailored shapes, is one of the most important semiconductors and has been widely used in photosensitizers, photo-Fenton reactions, and photocatalysis because of its deep suitable VB structure and its many intrinsic shape-dependent properties. [21][22][23] Many studies have confirmed that the properties of α-Fe 2 O 3 make it a good candidate for coupling with other semiconductors to construct Z-type heterojunctions with enhanced photoactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike inorganic and organometallic phosphors, [30][31][32][33][34] the fabrication of efficient pure organic RTP luminogens remains challenging, owing to the spin-forbidden intersystem crossing (ISC) process and the high susceptibility of phosphorescence to molecular motions and external quenchers. [3][4][5][7][8][9][10][11][12][13] Even though great advances have been achieved for the molecular design of pure organic RTP through incorporation of halogens, aromatic carbonyls, and heteroatoms, [7][8][9][10][11][12][13] as well as effective suppression of nonradiative processes by supramolecular interactions, [35,36] micelle stabilization, [37] absorption on solid substrate, [38] crystal-lization, [3,4,7,[15][16][17] embedding into rigid matrices, [5,23,39] chemical bonding to polymer chains, [14] etc., the development of pure organic RTP remains in its infant stage. Furthermore, persistent RTP (p-RTP) with naked eye visible emission after ceasing the excitation is even difficult to achieve, despite it has diverse promising applications in advanced OLEDs, bioimaging, encryption and anticounterfeiting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, persistent RTP (p-RTP) with naked eye visible emission after ceasing the excitation is even difficult to achieve, despite it has diverse promising applications in advanced OLEDs, bioimaging, encryption and anticounterfeiting. [5][6][7][8][9][10][11][12][40][41][42][43][44][45][46] So far, increasing examples have been explored in host-guest systems, [5,40] H-aggregates, [6,41,42] crystals [43][44][45][46][47][48][49][50] and even nonconventional luminogens free of aromatics, [51,52] the mechanism and rational design strategy, however, remain open questions.…”
Section: Introductionmentioning
confidence: 99%
“…While, the (002) plane with a 0.34 nm interplanar spacing is consisted with graphite. 40,41 In more detail, the corresponding EDS element mapping images are shown in Figure 3D and reveal uniform distribution of C, N, Ti, and O in TOCN. SEM images of sulfur particles and TOCN@S composite are displayed in Figure 3E,F.…”
Section: Resultsmentioning
confidence: 99%